Legal Implications of Personal Data Misuse in Emergency Contact Information for Online Loan Services - Dilla Haniah Kurniawati; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the legal risks associated with being an emergency contact or the absence of emergency contact in online loans. Utilizing a Normative Juridical approach, the research evaluates the effectiveness of legal policies in minimizing these risks. Findings reveal that serving as an emergency contact may lead to inconvenience due to frequent communication from debt collectors, while the absence of emergency contacts poses challenges for lenders in contacting borrowers, resulting in potential financial losses. These results underscore the importance of implementing efficient legal measures to protect both borrowers and lenders in online lending transactions. Highlights : Importance of Legal Policies: Evaluating the effectiveness of legal policies in minimizing risks associated with online loans is crucial for ensuring the protection of both borrowers and lenders. Role of Emergency Contacts: Investigating the impact of emergency contacts on mitigating legal risks sheds light on the practical aspects of borrower-creditor communication in online lending transactions. Financial Implications: Understanding the financial consequences of lacking emergency contacts in online loans underscores the need for comprehensive risk management strategies in the digital lending landscape. Keywords: Online loans, Legal risks, Emergency contacts, Normative Juridical approach, Financial implications